Impact of the transport system on air quality: the case of Rio de Janeiro, Brazil (Sustainability in Debate, 2022)
In the downtown area of Rio de Janeiro, Brazil, an urban mobility plan was implemented between 2011 and 2016 due to 2014 FIFA World Cup and the 2016 Olympic Games. This study aimed to evaluate the environmental benefits achieved by this urban mobility plan by comparing two periods: 2013 (before the megaevents) and 2017 (after the megaevents). Energy consumption and emissions from buses were estimated, and regulated pollutants (O3, CO, PM10, and PM2.5) were monitored. According to the calculations, NOx was the most emitted pollutant (60%). A 25% reduction levels for all pollutants was observed in 2017 compared to 2013. The reorganization of traffic shortened the bus routes, resulting in less fuel consumption (8%) and emissions. The annual mean concentrations of air pollutants (PM10, PM2.5, and CO) also decreased, thereby improving air quality. However, the levels of O3 increased, possibly owing to the reduction of NOx levels.